SOME WAYS OF IMPROVEMENT THE ELECTROPHOTOMETRIC INSTRUMENTS - Vovchyk, E.; Blagodyr, J.; Logvinenko, O.; Klym, B. (Одеські астрономічні публікації, 2017)
In the paper some ways of the improvement (changes in the optical-mechanical part and improvement in the electronical part) the electrophotometric instruments are described. The apparatus which were constracted at Lviv astronomical observatory were taken as the examples.